Design and Performance Analysis of a Low-Cost ESP32-Based NAT WiFi Repeater for Indoor IoT Networks - Oktrison; Dirja Nur Ilham; Rudi Arif Candra; Erwinsyah Sipahutar (Politeknik Aceh Selatan, 2025)
The rapid proliferation of indoor Internet of Things (IoT) systems has intensified the need for cost-effective and energy-efficient wireless coverage extension solutions. Conventional commercial WiFi repeaters are often over-provisioned in terms of hardware capability and power consumption, making them unsuitable for small-scale IoT laboratories and energy-constrained environments. Although microcontroller-based platforms such as the ESP32 have been widely used for IoT gateways, their systematic evaluation as Network Address Translation (NAT)-based WiFi repeaters remains limited. This paper presents the design, implementation, and experimental performance evaluation of a low-cost ESP32-based NAT WiFi repeater for indoor IoT networks. The proposed architecture operates in dual-mode (Station + Access Point) configuration using a single 2.4 GHz radio interface and software-based NAT forwarding. Hardware optimization, including Bluetooth deactivation and transmission power tuning, is applied to reduce energy overhead. Experimental measurements conducted in an indoor laboratory environment evaluate throughput, latency, received signal strength indicator (RSSI), and power consumption. Results indicate that the proposed system achieves 15–35 Mbps throughput under single-client conditions, with an average latency increase of 3–8 ms compared to direct router connections. The repeater improves signal strength by up to 18 dB in weak-coverage areas, extending effective indoor coverage by approximately 10–20 m. Measured power consumption remains below 1.2 W during active forwarding, significantly lower than typical commercial repeaters. The main contribution of this work lies in providing a quantified energy–performance characterization of a microcontroller-based NAT repeater.